Locating Violence in Kusum Kumar’s Suno Shefali (Listen Shefali) - Thakur, Vikram Singh (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2023)
India has a long tradition of social dramas that dates back to the 19th century. Such plays have been instrumental in raising social and political awareness among the masses. Located within this strong tradition of ‘socials’, is Kusum Kumar’s hard-hitting play Suno Shefali (Listen Shefali). Originally written in Hindi in 1975 and published in 1978, the play is significant for it engages with violence and oppression at the intersection of caste, class and gender at a time when feminist scholars had not theorized intersectionality as an important analytical tool of analysis. The play also predates several important Indian plays, especially by the male playwright, that deal with the problems of caste system in India. In this essay, I will attempt to study various forms of violence committed on a Dalit woman at the intersection of gender, caste and class in Kumar’s Listen Shefali using theoretical concepts like Kimberle Crenshaw’s ‘intersectionality’, Johan Galtung’s ‘structural violence’, M. Weigert’s ‘personal violence’, Pierre Bourdieu’s ‘symbolic violence’ and Gayatri Chakravarty Spivak’s ‘epistemic violence’.